Sastra sebagai Kritik Sosial : Ketidakadilan yang Dialami Masyarakat dalam Sajak ‘Orang Kepanansan’ Karya W.S Rendra - Dhini Kusuma Lestari; Dwi Wahyu Candra Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This article examines the role of literature as a medium for social criticism. Literature is not merely a collection of beautiful words; it also functions to convey emotions, ideas, and criticism regarding social issues. Literature can portray societal conditions and various issues veiled in public discourse, fostering debate, reflection, and acting as a catalyst for social change. This article specifically analyzes W.S. Rendra's poem